Cognitive function, daily function and physical and mental health in older adults: A comparison of venue and home-visit community surveys in Metropolitan Tokyo. (May 2022) - Sakuma, Naoko; Inagaki, Hiroki; Ogawa, Madoka; Edahiro, Ayako; Ura, Chiaki; Sugiyama, Mika; Miyamae, Fumiko; Suzuki, Hiroyuki; Watanabe, Yutaka; Shinkai, Shoji; Okamura, Tsuyoshi; Awata, Shuichi
Highlights: Cognitive health is essential for the healthy life of older people. We compared the venue and home-visit surveys in a sample of urban older people. Rate of cognitive decline measured by the MMSE was higher in the home-visit survey. Participants in the home visit-survey could be more difficult in their daily lives. Home-visit surveys can help increase the representativeness of older people. Abstract: Purpose: We conducted surveys in older people at a venue and in home-visits, and compared cognitive and health status between the two groups to assess their cognitive and everyday functioning. Methods: Among 7, 614 persons aged 70 years and older living in an urban area, 5, 430 responded to a mail survey for sociodemographic characteristics and self-rated questionnaires including the Geriatric Depression Scale-short form (GDS-15). Of these, 1, 360 agreed to attend a venue survey, and 693 agreed to take a home-visit survey. Trained nurses examined participants' blood pressure, medical history, and daily functions using the dementia assessment sheet for community-based integrated care system (DASC-21), and tested their cognitive function using the Mini-Mental State Examination (MMSE). Results: Of 2, 053 participants, 2, 020 (venue: 1, 352; home-visit: 668) completed the MMSE. Median MMSE scores for the venue and home-visit groups were 28 and 26 points, respectively, with 130/1, 352 (9.6%) and 205/668 (30.7%) participants below the traditional 23/24 cutoff score. The home-visit group had lower mobility, lower frequency of going out, poorer mental health, and lower independence in instrumental daily activities. Notably, 39.9% and 43.7% of the venue and home-visit groups lived alone, respectively. Conclusions: In this sample of urban older people, the rate of cognitive decline detected using the MMSE was three times higher in the home-visit group than in the venue group. Home-visit participants were more likely to have difficulty in physical, cognitive, and everyday functioning, suggesting they have a greater need for daily living support to continue living in the community.